Computer-based Prompt's impact on postural variability and sit-stand desk usage behavior; a cluster randomized control trial. (September 2019) - Garrett, Gregory; Zhao, Hongwei; Pickens, Adam; Mehta, Ranjana; Preston, Leigh; Powell, Amy; Benden, Mark
Abstract: Sit-to-stand workstations have been deployed in office environments to reduce sedentary behavior and improve worker's health. However, efforts to initiate and sustain long-term usage of sit-stand workstations has been a challenge, with primarily anecdotal evidence suggesting many employees cease using their sit-stand workstations once the newness diminishes. To objectively determine sit-stand workstation usage and what impact computer-based prompts would have on sit-stand desk use and sustainability, 200 office workers (118 control and 82 treatment) in two different geographic locations were continuously monitored over a 4 ½ month period, which consisted of a 6-week baseline and a 3-month experimental period. During the 3-month experimental period, computer-based prompts elicited a 229% increase in daily standing transitions which was sustained over the entire 3 months with 40% of the participants adhering to a pre-determined sit to stand schedule. These findings indicate that the use of computer-based prompts can be used to motivate employees to change their behavior regarding the use of sit-to-stand workstations. Highlights: Computer-based prompts increase sit-stand desk usage. Perceived health benefits of sit-stand desk transitions increase usage. Internal motivation linked to increased sit-stand desk usage. Computer-based prompts increased perceived mental focus and productivity.